The Role of The Republic of Uzbekistan in Developing Cooperation with Countries within the Framework of The Commonwealth of Independent States in The XXI Century (Eurasian Journal of Humanities and Social Sciences, 2023)
This article discusses the cooperation relations of the CIS countries and development strategies of Uzbekistan within the CIS